Analisys Factors Affecting Employee Performance in Lubuk Baja District Batam City - Siregar, Anugrah Aditeo Alexsander; Windayati , Diana Titik; Suhardis, Adnan (Universitas Batam, 2023)
The study analyze the effect of workload, work morale, and work motivation on employee performance in Lubuk Baja Dictrict Batam City. The method applied in this study is the quantitative method and used SPSS version 25 software to process the data. The population in this study were employees of Lubuk Baja District, totaling 66 people and taking samples of 66 respondents. Results from the partial t-test revealed that workload, work morale, and work motivation significantly influenced employee performance. And these factors were considered together, they collectively showed a considerable impact on employee performance in Lubuk Baja Dictrict Batam City. The coefficient of determination value of 30.3% could be attribute of workload, work morale, and work motivation and the majority, accounting 69.7%, attribute by another variables not explore